Using Routine Ambulance Inspection Report Application to Reduce Wasted Time in Emergency Medical Services - Apiratwarakul, Korakot; Ienghong, Kamonwon; Suzuki, Takaaki; Celebi, Ismet; Bhudhisawasdi, Vajarabhongsa; Tiamkao, Somsak (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Ambulance inspections make up part of the emergency medical services (EMS) to keep operations running smoothly as well as to maximize and maintain the safety of vehicles used for delivery of both staff and patients. The EMS of Srinagarind Hospital has been using an ambulance inspection report application since January 2020. Nevertheless, there has been no comparative study of the benefits associated with the use of this specification. AIM: The aim of this study was to compare the advantages of an ambulance inspection report application and paper checklist. METHODS: This cross-sectional study was conducted amid the EMS at a university hospital in Thailand. Data gathering was carried out by employing the Srinagarind Hospital database and ambulance inspection report application throughout January 1, 2019, and December 31, 2020. RESULTS: A total of 2350 ambulance inspections were recorded during the 2-year study period. Recognition times for ambulance inspections incorporating paper checklist and inspection with application were 35.5 ± 9.4 min and 1.02 ± 0.5 min, respectively (P < 0.001). Action times were 25.2 ± 5.1 min and 1.04 ± 0.2 min, respectively. Ambulance inspection compliance rate with the application was 95.3% and 70.1% with a paper checklist. CONCLUSION: Ambulance inspections carried out with an application can reduce recognition and action time, and increase ambulance inspection compliance rate.